2020
DOI: 10.3390/ijms21239007
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aging Rheological Behavior of Magnetorheological Elastomers Based on Silicone Rubber

Abstract: Engineering rubber composites have been widely used as main components in many fields including vehicle engineering and biomedical applications. However, when a rubber composite surface area is exposed to heat or sunlight and over a long-term accelerated exposure and lifecycle of test, the rubber becomes hard, thus influencing the mechanical and rheological behavior of the materials. Therefore, in this study, the deterioration of rheological characteristics particularly the phase shift angle (δ) of silicone ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…Surface defects were possibly due to the evolution of low molecular degradation products, which allow the penetration of water and possible decomposing agents (e.g., enzymes) into the bulk of the polymer and facilitate further environmental degradation. This phenomenon was also found by other researchers who tested MRE with thermal aging [27].…”
Section: Micrograph Analysissupporting
confidence: 84%
“…Surface defects were possibly due to the evolution of low molecular degradation products, which allow the penetration of water and possible decomposing agents (e.g., enzymes) into the bulk of the polymer and facilitate further environmental degradation. This phenomenon was also found by other researchers who tested MRE with thermal aging [27].…”
Section: Micrograph Analysissupporting
confidence: 84%
“…Surface defects is possibly due to the evolution of low molecular degradation products, allow the penetration of water and possible decomposing agents (e.g, enzymes) into the bulk of the polymer and facilitate further environmental degradation. This phenomenon was also found by other researcher which tested MRE with thermal aging [27].…”
Section: Micrograph Analysissupporting
confidence: 81%
“…In fact, the initial loss factor was also enhanced due to an interfacial defect caused by thermal aging, which resulted in a higher interfacial damping. Recently, Aziz et al [33] studied the deterioration of rheological properties related to the phase shift angle (δ) of SR-based MRE with 60 wt% under the effect of thermal aging. The results demonstrated that the temperature has altered and simultaneously increased the phase shift angle (δ) along the strain, predominantly at a higher strain (>1%).…”
Section: Introductionmentioning
confidence: 99%